Age and habitat quality matters: isotopic variation of two sympatric species of rodents in Neotropical Forest - Bovendorp, Ricardo Siqueira [UNESP]; Simoes Libardi, Gustavo; Moraes Sarmento, Mariana Montagner de; Camargo, Plinio Barbosa; Percequillo, Alexandre Reis (Assoc Teriologica Italiana, 2017)
Dietary studies allow us to understand important ecological patterns such as intra- and interpopulation variation and interspecific differences regarding the use of food sources. Stable isotopes have been successfully employed to detect dietary differences between species and feeding shifts within a species, as a response to age, habitat use, and resource availability. Here we investigated the stable isotope compositions of carbon and nitrogen of young and adult specimens of Euryoryzomys russatus and Sooretamys angouya and their stomach contents, in a complex mosaic of vegetation in the Brazilian Atlantic Forest. Isotopes indicated a pronounced inter- and intraspecific plasticity in resource use for E. russatus and S. angouya. Plant sources were the prevalent feeding itens for E. russatus, with low to intermediate consumption of arthropods. For S. angouya, plants were dominant in the stomach content, but arthropod arose as an important source. E. russatus showed more variation in isotopic signature between grids than S. angouya, suggesting that the former was more affected by habitat changes. These results allow us to better understand the ontogeny, diet and the behavioral responses to environmental variations of both species. Finally, our study contributes to reduce the lack of knowledge about sympatric species ecology and aggregates information for their conservation.
Keywords: Atlantic Tropical Forest; Euryoryzomys russatus; Sigmodontinae; Sooretamys angouya; stomach contents